Analysis of Digital Television User Acceptance After Analog Switch-Off (ASO) Implementation in Jabodetabek - Arwidya Tantri Agtusia; Akhmad Sarif; Ajib Setyo Arifin (Jurnal E-Komtek, 2023)
The government officially stopped broadcasting analog television or what is known as Analog Switch Off (ASO) on November 2, 2022, in Jabodetabek. It impacts analog TV users in Jabodetabek, who can no longer receive television broadcasts on their analog televisions. This research aimed to determine user acceptance of digital television broadcasts after implementing ASO in the Jabodetabek area. In the present study, the experience of digital TV users is evaluated using the UTAUT (Unified Theory of Acceptance and Use of Technology) 2 model and the Structural Equation Model (SEM). The data was obtained from a questionnaire distributed through digital media for the Jabodetabek area. According to data processing, the two factors that significantly influence the user experience of digital television broadcasts are the Analog Switch Off (ASO) policy factor and the habit factor. The hypothesized model suitability test fits the resulting data and can affect the Behavioral Intention 41.4.